2021
DOI: 10.1136/jclinpath-2021-207425
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on small biopsy diagnostic procedures and cancer resection surgeries in the North-West of Ireland

Abstract: AimsTo quantify the impact of COVID-19 on small biopsy procedures and cancer resection surgeries in the North-West of Ireland.MethodsData was obtained from the Histopathology Departments of University Hospital Galway (UHG) and Letterkenny University Hospital (LUH) Laboratory Information Systems to establish the impact of COVID-19 on both the small biopsy (coded P01) and cancer resection (coded P03) caseloads reported from January to June 2020, with comparison made to January to June 2019.ResultsFrom January to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 11 publications
3
7
0
Order By: Relevance
“… 3 Reductions in cancer diagnoses similar to those in Ontario have been reported elsewhere. 4 , 5 , 7 , 12 , 13 , 14 , 15 , 16 , 17 In line with our findings, a study from Italy reported a 17% reduction in radiotherapy. 18 Another study from Spain reported reductions of 37% in new oncology referrals and 38% in new treatments, 19 substantially greater reductions than those observed in Ontario.…”
Section: Discussionsupporting
confidence: 92%
“… 3 Reductions in cancer diagnoses similar to those in Ontario have been reported elsewhere. 4 , 5 , 7 , 12 , 13 , 14 , 15 , 16 , 17 In line with our findings, a study from Italy reported a 17% reduction in radiotherapy. 18 Another study from Spain reported reductions of 37% in new oncology referrals and 38% in new treatments, 19 substantially greater reductions than those observed in Ontario.…”
Section: Discussionsupporting
confidence: 92%
“…Concerning surgeries and loco-regional therapies, 106 indicators were identified from 30 articles [42,48–51,55,62,65,65,75,81,90,92–94,97–99,101–103,111,118–125]. Of those, 82 indicators (79%) showed a reduction in the number of treatment procedures, namely in Italy, France, Germany, Ireland, Netherlands, Spain, Turkey, UK, US, Australia, and in 1 international study.…”
Section: Resultsmentioning
confidence: 99%
“…The next stage of the care pathway focuses on diagnosis and staging. The "number of diagnostic, surveillance and staging procedures" was reported in 17 articles [41,[43][44][45][48][49][50][51][52][53][54][55][56][57][58][59][60] (from the UK, Italy, US, France, Australia, the Netherlands, Turkey, Ireland, and Slovenia), comprising a total of 90 indicators. Most of those indicators (n=58, 64%) showed a decreasing trend in the number of procedures, namely cystoscopy, diagnostic mammograms, breast cancer wire-guided biopsy, gastroscopy, colonoscopy, computed tomography (CT), magnetic resonance imaging (MRI), and endoscopic retrograde cholangiopancreatography.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, a reduction was observed in the pathology diagnoses of neoplasms of the lip, oral cavity, and pharynx; larynx, colon, rectum, and anus; kidney, melanoma, prostate, and urinary system; as well as the central nervous system. With particular regard to tumors of the central nervous system and the head and neck, it is possible that much of the diagnoses were based solely on imaging tests and that more conservative treatments with radiation therapy were opted for given the reduction in the number of surgeries, and the difficulty of accessing high-tech operating rooms and consequently in obtaining tumor samples in certain locations during COVID-19 [ 28 , 29 ]. Nevertheless, discrepant data have been found on the use of radiation therapy during the pandemic to date.…”
Section: Discussionmentioning
confidence: 99%